A sociological assessment of conjugal conflict - Giudici, Francesco (2016)
A sociological explanation of conjugal conflict was often stressed but seldom empirically tested. Based on a two-wave longitudinal dataset of 1534 women in heterosexual relationships, we use structural equation modeling (SEM) to measure the impact of the division of household labor, individualism and conjugal closure on the likelihood of conjugal conflicts. Results indicate that conjugal individualism has a major impact, division of household labor a minor impact, and conjugal closure no impact, on conjugal conflict. Results are discussed in the light of current sociological debates on partnerships.